Temporary Migration and Economic Assimilation - Christian Dustmann (Institute for the Study of Labor (IZA), 2000)
In this paper, I study temporary migrations, and its consequences for immigrants' behaviour. I distinguish between temporary migrations where the return time is exogenous, and temporary migrations where the migrant chooses when to return. I then illustrate the consequences both types of temporary migration have for migrants' behaviour (as opposed to a permanent migration). If migrations are non-permanent, then this has also consequences for the way empirical models need to be specified. The problems arising for empirical work are discussed in the second part of the paper. Finally, I summarise some empirical evidence which is consistent with the hypothesis that the behaviour of temporary migrants is different from that of migrants with permanent migration intentions.
Keywords: D9; F22; J24; 330; Human capital; temporary migration; Internationale Arbeitsmobilität; Saisonarbeitskräfte; Soziale Integration; Bildungsinvestition; Arbeitsmarktforschung; Theorie; USA; Deutschland